Global prevalence of cerebral palsy: A systematic analysis. (11th August 2022) - McIntyre, Sarah; Goldsmith, Shona; Webb, Annabel; Ehlinger, Virginie; Hollung, Sandra Julsen; McConnell, Karen; Arnaud, Catherine; Smithers‐Sheedy, Hayley; Oskoui, Maryam; Khandaker, Gulam; Himmelmann, Kate; ,
Abstract: Aim: To determine trends and current estimates in regional and global prevalence of cerebral palsy (CP). Method: A systematic analysis of data from participating CP registers/surveillance systems and population‐based prevalence studies (from birth year 1995) was performed. Quality and risk of bias were assessed for both data sources. Analyses were conducted for pre‐/perinatal, postnatal, neonatal, and overall CP. For each region, trends were statistically classified as increasing, decreasing, heterogeneous, or no change, and most recent prevalence estimates with 95% confidence intervals (CI) were calculated. Meta‐analyses were conducted to determine current birth prevalence estimates (from birth year 2010). Results: Forty‐one regions from 27 countries across five continents were represented. Pre‐/perinatal birth prevalence declined significantly across Europe and Australia (11 out of 14 regions), with no change in postneonatal CP. From the limited but increasing data available from regions in low‐ and middle‐income countries (LMICs), birth prevalence for pre‐/perinatal CP was as high as 3.4 per 1000 (95% CI 3.0–3.9) live births. Following meta‐analyses, birth prevalence for pre‐/perinatal CP in regions from high‐income countries (HICs) was 1.5 per 1000 (95% CI 1.4–1.6) live births, and 1.6 per 1000 (95% CI 1.5–1.7) live births when postneonatal CP was included. Interpretation: The birth prevalence estimate of CP in HICs declined to 1.6 per 1000 live births. Data available from LMICs indicated markedly higher birth prevalence. What this paper adds: Birth prevalence of pre‐/perinatal cerebral palsy (CP) in high‐income countries (HICs) is decreasing. Current overall CP birth prevalence for HICs is 1.6 per 1000 live births. Trends in low‐ and middle‐income countries (LMICs) cannot currently be measured. Current birth prevalence in LMICs is markedly higher than in HICs. Active surveillance of CP helps to assess the impact of medical advancements and social/economic development. Population‐based data on prevalence and trends of CP are critical to inform policy. What this paper adds: Birth prevalence of pre‐/perinatal cerebral palsy (CP) in high‐income countries (HICs) is decreasing. Current overall CP birth prevalence for HICs is 1.6 per 1000 live births. Trends in low‐ and middle‐income countries (LMICs) cannot currently be measured. Current birth prevalence in LMICs is markedly higher than in HICs. Active surveillance of CP helps to assess the impact of medical advancements and social/economic development. Population‐based data on prevalence and trends of CP are critical to inform policy. This paper determined the current birth prevalence of cerebral palsy in high‐income countries has declined to 1.6/1000 live births. Birth prevalence for low‐ and middle‐income countries is markedly higher. This original article is commented on by Paneth and Yeargin‐Allsopp on pages 1436–1437 of this issue.